IJCM_156A: A Cross-sectional study on the Prevalence of Risk Factors of Breast Cancer and Awareness of Breast Cancer Screening in Women of age group 30 to 70 years in Karamadai Block of Coimbatore Health Unit District - Divya V; Maheshwari Uma R; Damodaran V (Wolters Kluwer Medknow Publications, 2024)
Background: Breast cancer, the most common malignancy among women globally, recorded over 2.26 million new cases and almost 685,000 deaths in the same year. Evidence indicates breast cancer risk links to both modifiable and non-modifiable lifestyle factors. Promoting education and access to screening programs is crucial for early detection and intervention in breast cancer. This approach ultimately enhances the effectiveness of prevention efforts and reduces complications and mortality of breast cancer. Objective: To estimate the prevalence of risk factors of breast cancer and to assess the awareness of breast cancer screening in women of age group 30-70 years in Karamadai Block of Coimbatore Health Unit District. Methodology: A cross sectional study was conducted among 150 women in Coimbatore using a semi-structured questionnaire and statistical analysis was done using SPSS 21 version. Results: Out of 150 participants, the mean age of subjects was 50 Â± 11 years, with 98% being married women. The prevalence of modifiable and non- modifiable risk factors of breast cancer were found to be 61% and 9% respectively. 54% were aware of government facility-based breast cancer screening. But only 25% had undergone screening for breast cancer. Individuals who underwent breast cancer screening in the last one year found to be aware of breast cancer screening compared to those who did not. (OR 2.5, 95% CI 2.02-3.18). Conclusion: Awareness and screening for breast cancer are low among the study participants. Women =30 years of age attending all outpatient departments in any health facility should be educated regarding the importance of screening of breast cancer.